2019
DOI: 10.1111/vox.12867
|View full text |Cite
|
Sign up to set email alerts
|

HIV residual risk in Canada under a three‐month deferral for men who have sex with men

Abstract: Background and objectives In Canada, the deferral for men who have sex with men (MSM) was decreased from a permanent deferral to a 5‐year then a 12‐month deferral. Current HIV testing can detect an HIV infection in donated blood within 2 weeks of exposure; thus, a 12‐month deferral may be unnecessarily restrictive. We aimed to estimate the residual risk of HIV if the deferral were further decreased to 3 months. Materials and methods Using a deterministic model with stochastic Monte Carlo simulation, residual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…Even though our data are in agreement with the mentioned reports [2,[4][5]7,8], local epidemiological context is complex and different. In this sense, during recent years, there has been an increase in the incidence of STI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Even though our data are in agreement with the mentioned reports [2,[4][5]7,8], local epidemiological context is complex and different. In this sense, during recent years, there has been an increase in the incidence of STI.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a study by Suligoi et al [5] in 2013 demonstrated that after the change of donor screening criteria introduced in Italy in 2001, no significant increase in the proportion of MSM compared to heterosexuals was observed among HIV antibody-positive blood donors. Modelling studies performed in the US, Canada, UK and France evaluating several scenarios predicted negligible risk increments (less than 1 in 1 million units) when changing to a 12-month deferral period [2,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In Canada, 3-month deferral was introduced on June 3, 2019, after a similar analysis highlighted no increased risk to the safety of blood products intended for transfusion. 24,25 In S2, to estimate the number of additional MSM donors compliant with the selection criterion, we used the proportion of MSM with only one sexual partner in the previous 6 months reported in ERAS 2017 (30.4%). 10,11 This percentage would likely be higher for a shorter duration of 4 months, which would suggest an underestimation of the number of compliant MSM.…”
Section: Discussionmentioning
confidence: 99%
“…7 That same year, Canada also changed from a 12-month to a 3-month deferral, again based on a favorable risk assessment. 8 Although the data have not yet been published, it appears that this policy change has had, once again, no measurable impact on the prevalence of HIV in the donor population of these two countries. The predictions made by the Pillonel model are therefore in agreement with these preliminary observations.…”
mentioning
confidence: 99%